South Africa online media coverage of intimate femicide: a content analysis comparing coverage between 1 November 2014 to 30 April 2015 and 1 November 2016 to 30 April 2017 - Silima, Mpho (My University, 2019)
Background: South Africa has one of the highest femicide rates in the world and it is the leading cause of death amongst South African women. The media is key in shaping how people in society think and the manner in which the media reports on issues of femicide has an impact in the way in which society deals with it. Although extreme cases of physical violence such as femicide often make it on the news, it is media coverage of other forms of VAW that are the topic of published research, therefore content analysis on femicide coverage in particular contributes to the gap in the current literature. Aim: The overall aim of the study was to describe and compare South African online media coverage of Femicide during the periods 1 November 2014 to 30 April 2015 and 1 November 2016 and 30 April 2017. Methods: A descriptive study utilizing content analysis was carried out. All online news articles available through the Media Monitoring Africa database during the period 1 November 2014 to 30 April 2015 and 1 November 2016 to 30 April 2017 were eligible for inclusion in the study. All articles discussing femicide or making mention of the phenomenon from the two periods were analysed with the aim of ensuring that there was the greatest possible representation during that particular period. Online articles were captured and coded for the 2014/2015 and 2016/2017 periods using Media Monitoring Africa software, Dexter. The content for analysis derived from each item was descriptive and frequency tables and graphs were used to show the frequency and the proportions of the content. Results: A total of 291 and 141 articles during the 2014/2015 and 2016/2017 period respectively reported on femicide stories. The frequency of femicide coverage in South Africa over the period was very low with majority of the stories in both periods coming from the metropolitan areas and focusing on a handful of key femicide cases that dominated coverage. Two of the dominant stories were of husbands hiring hit men to kill their wives, where the one ended in conviction whilst the other was acquitted for the crime. The quality of reporting across both periods was found to be sub-standard in all indicators under study, lacking critical investigation and provision of context which would place intimate femicide as part of a broader social issue. In terms of how the perpetrators and victims were portrayed results found that there was very limited victim blaming and exonerating the perpetrator for his actions. Consistent with previous research the most widely accessed sources to provide information on the femicide case were from the criminal justice and law enforcement system, and majority of these were male. Conclusion: This study has shown that although South Africa has excessive rates of intimate femicide the issue is not taken seriously in the media. The research has highlighted that overall coverage of femicide is overly-simplistic, inadequate and portrays distorted representations of the extent and nature of the problem. Societal reactions in particular those of policy makers based on inaccurate media portrayals have the potential to result misguided interventions and strategies in addressing intimate femicide, therefore it is imperative that media portrayal of violence against women represents the true nature of the issue.
A research report submitted in partial fulfilment of the requirement for the award of the degree of Master of Public Health Faculty of Health Sciences , University of the Witwatersrand June, 2019